Hemimycena longipleurocystidiata (Mycenaceae, Agaricomycetes), a new species from the Argentinean Atlantic Forest - Niveiro, Nicolás; Popoff, Orlando Fabian; Albertó, Edgardo (Phytotaxa, 2014)
The Atlantic Forest is the second largest South American tropical-subtropical rainforest and one of the most diverse ecosystems on earth. Hemimycena longipleurocystidiata, a fungal species collected in the Argentinean Atlantic forest, is proposed as new. It is characterized by its whitish and large basidiomata with large pleuro- and cheilocystidia. The species is here described and illustrated and a key is provided to the Hemimycena species known from Argentina.